The Impact of Guidance Programme in Enhancing Self-Esteem for Risk Behaviour Change among Youth Living with HIV/AIDS in Nakuru County, Kenya - Kariuki, Reuben G; Muola, James M; Chemwei, Benard (The Africa Premier Research Publishing Hub, 2017)
This is from an experimental study, which assessed the impact of Guidance Programme in enhancing Self-Esteem among Youth Living with HIV in Nakuru county Kenya. A sample of 76 YLWHA was randomly assigned into an experimental (N=38) and control groups (N=38). Guidance programme was administered to the experimental group. Findings showed that guidance programme enhanced positive self-esteem, and hence enhanced risky behaviour change among the YLWHA. The target population was 57,800 PLWHA in the County. Quantitative and qualitative data were collected through a questionnaire and an interview schedule. Validity of the instruments was checked through expert’s opinion and piloting to a similar population with similar characteristics and critically looking at the objectives. Cronbach’s alpha method was used to test reliability. The corrected item total correlation for pre-test and post-test for self-esteem had a Cronbach’s alpha of 0.804 for pre-test and 0.786 for post-test respectively. These values are well above the threshold for a scale which is 0.7. T-test for independent means was used to determine the difference between means of the two groups, the experimental and the control group. The percentiles and the chisquare were also used for verifications. The tests were calculated at, 0.05 level of significance. The Statistical Packages for Social Sciences (SPSS) windows version 22.0 was used to analyze quantitative data. The findings of the study revealed that the guidance programme had an impact on self-esteem. This study will hopefully be used to improve establishment and development of effective risk reduction behavior programmes for YLWHA by all stakeholders. The study recommends that the Guidance programme be incorporated in all intervention programmes for PLWHA
Keywords: Guidance programme; Self-Esteem; Risky Behaviour Change; YLWHA